Rethinking National Identities in Indonesian Education Curriculum - Ella Masita (Jurnal Bahasa dan Sastra, 2018)
Abstract: This article explores the conceptualization of Indonesian national identity from the point of view of the Indonesian government. The data is taken from the three most recent In- donesian national curricula and its prescription in mandated English textbooks for senior high school. It interrogates the dimensions in an Indonesian context of the 2004 Curriculum as the first national curriculum in Indonesia after the fall of Soeharto’s regime, in 2006 Curriculum as Indonesia reconsidered its position within a global competitive world context, and in 2013 to respond to perceptions of unsatisfactory education results and a looming ‘identity crisis’. Vis- iting the key issues within those documents and the corresponding English textbooks through the lens of Representation theory as suggested by Hall (1997), the article explores the complex interconnections that frame the curriculum discussion. Three main findings are emerged in relation how the national identity concepts are shifting over time in those three consecutive curricula namely: from the interpretive to prescriptive curriculum, from operational to notional curriculum, and from other-ness to us-ness imagined communities.Keywords: Curriculum, English language teaching, national identityAbstrak: Artikel ini mengeksplorasi konsep identititas nasional ditinjau dari sudut pandang pemerintah Indonesia. Data diambil dari tiga kurikulum pendidikan nasional terakhir bersama dengan buku pelajaran Bahasa Inggris untuk SMA. Ketiga kurikulum tersebut adalah Kuriku- lum 2004, Kurikulum 2006,dan Kurikulum 2013. Kurikulum 2004 diambil sebagai kurikulum pendidikan nasional pertama di Indonesia setelah jatuhnya pemerintahan presiden Soeharto pada tahun 1998. Sementara itu, Kurikulum 2006 adalah kurikulum pendidikan nasional di In- donesia untuk memeprsiapkan generasi muda Indonesia dalam konteks persiangan global. Se- baliknya, Kurikulum 2013 disahkan pemerintah Indonesia sebagai kurikulum resmi di system pendidikan nasional Indonesia sebagai respons dari adanya persepsi tentang asil pendidikan yang kurang memuaskan dan adanya “kriris identitas” di kalangan generasi muda Indonesia. Melalui landasan teori Representation (Hall, 1997), artikel ini mengupas tentang bagaimana konsep identitas nasional bergeser dalam ketiga kurikulum tersebut. Terdapat tiga temuan uta- ma: perubahan dari interpretive menjadi prescriptive, dari operational menjadi notional, dan dari “other-ness’ menjadi “us-ness” imagined communities. Artikel ini berfokus pada temuan tentang perubahan kurikulum tersebut.Kata-kata kunci: Kurikulum, pengajaran Bahasa Inggris, identitas nasional